The relationship between self-concept, self-efficacy, emotional state, weight perception and food choice : implications for marketers based on a Generation Y sample - Janse van Rensburg, Louise (Stellenbosch : University of Stellenbosch, 2011)
Thesis (MComm (Business Management))--University of Stellenbosch, 2011.